The Implementation of India’s Maritime Doctrine to Respond China Naval Presence in Indian Ocean Region - Anak Agung Banyu Perwita; Fadhlur Rivanda (Indonesian Journal of Peace and Security Studies (IJPSS), 2020)
Indian Ocean is a strategic and crucial location of the region and became the centre of global politics. Indian Ocean Region (IOR) has several important gulfs, straits, bays and seas within which most of it located in the northern part of the ocean. Major shipment routes intersect its enormous area, with crucial choke points and water courses connecting Indian Ocean to other main ocean parts on the earth. Indian Ocean region is part of China’s significant security interests, where China is currently leading to an ever advanced military existence within the area. China’s overpowering strategic focus in the Indian Ocean is the preservation of their maritime trading routes, particularly those transporting oil and gas that the Chinese economy relies upon. Indian Ocean Region is at the top of Indian policy priorities. India’s vision for Indian Ocean Region is deep-rooted in preceding cooperation in the region and to use their capabilities for the benefit of all in their common maritime home. The Indian Ocean holds particular importance for India. India is definitely trying to maintain their national security interests in Indian Ocean. In response to the condition in the Indian Ocean, India implemented its Indian Maritime Doctrine which is applied through Indian Navy as the way to respond China’s naval existence in IOR since 2008. This implementation brings the sources of its naval application as an effort to balance China’s naval presence in IOR through its doctrine. The unilateral naval effort is held to respond China in IOR. Moreover, a further effort of Indian navy is needed through bilateral cooporation that will further support its unilateral effort in balancing China’s active presence in the region.